Scientology 8-80 : The discovery and increase of life energy in the genus homo sapiens - Hubbard, L. Ron (California Bridge Publications, Inc, 2007)
The first explanation of the electronics of human thought and the energy phenomena in any being. Discover how even physical universe laws of motion are mirrored in a being, not to mention the electronics of aberration. Here is the link between theta and MEST revealing what energy is, and how you create it. It was this breakthrough that revealed the subject of a thetan$1 (Bs flows and which, in turn, is applied in every auditing process today. In the book$1 (Bs title, (3z(B8-8(3y (Bstands for Infinity-Infinity, and (3z(Sk(3y (Brepresents the static, theta. Included are the Wavelengths of Emotion, Aesthetics, Beauty and Ugliness, Inflow and Outflow and the Sub-zero Tone Scale$1 (Bapplicable only to the thetan.s
Keywords: NON TECHNICAL BOOKS (NTB)